Implementasi Projek Penguatan Profil Pelajar Pancasila (P5) Berkarya Melalui Sampah Di SDN Banua Anyar 9 - Amalia Rizkina; Adetya Nor Rizkyka (Fakultas Pendidikan, Universitas Sultan Muhammad Syafiuddin Sambas, 2025)
The aim of this research is to address observed issues in schools where the surroundings appear unclean with scattered litter. Poor management practices serve as a warning to take concrete actions towards creating a clean, comfortable, and waste-free school environment. Based on this, SDN Banua Anyar 9 implemented